Will porcine somatotropin (pST) lower pork quality? - Melvin C Hunt; Patter G Whipple-Van; R D Klemm; B R Schricker; Robert D Goodband; Jim L Nelssen; Robert H Hines; Donald H Kropf (Kansas Agricultural Experiment Station Research Reports, 1989)
The types and diameters of muscle fibers from 30 barrows that had received daily injections of porcine somatotropin (pST) or a placebo and were fed dietary lysine at .6, .8, 1.0 or 1.2% were determined. Fiber data indicated that pST slightly increases the anaerobic metabolic potential of longissimus muscle. The higher levels of lysine caused enlargement of muscle cells. Earlier research has shown that this type of muscle biochemistry contributes to development of PSE muscle. Thus, use of pST in certain strains of pigs may lead to reductions in muscle quality.; Swine Day, Manhattan, KS, November 16, 1989
Keywords: Swine day; 1989; Kansas Agricultural Experiment Station contribution; no. 90-163-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 581; Swine; Porcine somatotropin; Lysine; Pork quality